The Proper Use of Safety Harness Among Workers In A Maintenance Company - aziz, nadzmi (Progress in Engineering Application and Technology, 2023)
Most of the employees of Harta Infra Legacy Snd.Bhd does not use safety harnesses when working at the height as expected. However, employees are continuously exposed to hazards when working at height places, and the use of safety equipment is required by laws such as the OSHA Amendment 2022. Objective of this research is to the prevalence of the proper use of safety harnesses among workers in the maintenance industry, to analyzed factors of lacking in safety harness usage among employees, and to suggest control measures to encourage employees to wear full body harnesses properly while performing work at height. Structured questionnaire produced according to the objective consisting of four part was used for data collection, and the respondents were Harta Infra Legacy Snd.Bhd employees. The reason for workers’ lack of use of safety harnesses is identified through theoretical analysis, descriptive statistics, correlation analysis, and regression analysis. 36 employees of Harta Infra Legacy have answered a questionnaire based on specific variables. that attitude is the main cause of workers not wearing safety harnesses. Therefore, the attitude has been workers do not wear a safety harness. This analysis shows that the discomfort of using safety harnesses, and lack of knowledge about how to use safety harnesses are why employees do not use safety harnesses when working at heights. control measures proposed to encourage the use of safety harnesses among workers are to provide more safety training and focus on training the use of safety harnesses correctly and make the worker aware of the hazard they will face if wearing the harnesses in the wrong way.